Anti-inflammatory Flavonoid C-Glycosides from Piper aduncum Leaves - Thao, Nguyen Phuong; Luyen, Bui Thi Thuy; Widowati, Wahyu; Fauziah, Nurul; Maesaroh, Maesaro; Herlina, Tati; Manzoor, Zahid; Ali, Irshad; Koh, Young Sang; Kim, Young Ho (Planta Medica, 2016)
Four new compounds, acacetin 8-C-[β-D-apiofuranosyl-(1 → 2)-β-D-glucopyranoside] (1), 7-methoxyacacetin 8-C-[β-D-apiofuranosyl-(1 → 3)-β-D-glucopyranoside] (2), 7-methoxyacacetin 8-C-[β-D-glucopyranosyl-(1 → 2)-β-D-glucopyranoside] (3), and 4‴-O-acetylacacetin 8-C-[α-L-rhamnopyranosyl-(1 → 2)-β-D-glucopyranoside] (4), along with ten known compounds (5–14), were isolated from Piper aduncum leaves. The effects of these compounds on lipopolysaccharide-induced expression of the proinflammatory cytokines IL-12 p40, IL-6, and TNF-α in bone marrow-derived dendritic cells were evaluated. Compounds 2, 3, 6, 8, 9, and 11–13 inhibited the production of both IL-12 p40 and IL-6, with IC50 values ranging from 0.35 ± 0.01 to 1.40 ± 0.04 µM and 1.22 ± 0.02 to 3.79 ± 0.10 µM, respectively. Compounds 5 and 10 only showed strong inhibition effects on the production of IL-12 p40, with IC50 values of 2.76 ± 0.08 and 0.39 ± 0.05 µM, respectively. However, all compounds showed weak activity or no activity on TNF-α production at the tested concentrations.
Keywords: Piper aduncum; Piperaceae; Flavonoid C-glycoside; IL-12 p40; IL-6; TNF-α; LPS